Biomechanical report for the IAAF World Championships London 2017 triple jump men's - Tucker, C.; Nicholson, G.; Cooke, M.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The men`s triple jump finals took place on the night of August 10th in warm and still weather conditions. Coming into the final, Christian Taylor and Will Claye, both of the USA, were strong contenders given their season leading performances. The final was a battle between the two Americans for the gold. Taylor`s third round jump of 17.68 metres in response to Claye`s jump of 17.63 metres was enough to win him the gold medal. Claye`s jump was enough to secure the silver medal position. Portugal`s Nelson Évora earned the bronze medal with a third round jump of 17.19 metres. (Attention! registration on the IAAF site is required for downloading)